2012
DOI: 10.5194/nhess-12-2659-2012
|View full text |Cite
|
Sign up to set email alerts
|

A lightning climatology of the South-West Indian Ocean

Abstract: The SWIO is characterized by a wet season (November to April) and a dry season (May to October). As one could expect, lightning activity is more intense during the wet season as the Inter Tropical Convergence Zone (ITCZ) is present over all the basin. Flash density is higher over land in November-December-January with values reaching 3-4 fl km −2 yr −1 over Madagascar. During the dry season, lightning activity is quite rare between 10 • S and 25 • S. The Mascarene anticyclone has more influence on the SWIO res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 63 publications
2
26
0
3
Order By: Relevance
“…Although few studies have examined the interdependency of the Mascarene High and MJO, Pohl et al (2009) an intraseasonal modulation of the Mascarene High and MJO by applying a principal component analysis. The variations in the environmental conditions and convection during P1 and P2 are consistent with a previous study showing that the Mascarene High generally inhibits convection owing to the trade inversion (Bovalo et al 2012). During the mature period of P4, a strong extratropical cyclone appears to the south of 20°S, and its appearance is synchronized with the local minimum pressure of less than 1008 hPa in the equatorial region and the intensification of the MJO convection (Fig.…”
Section: Large-scale Environmental Conditions Aroundsupporting
confidence: 90%
“…Although few studies have examined the interdependency of the Mascarene High and MJO, Pohl et al (2009) an intraseasonal modulation of the Mascarene High and MJO by applying a principal component analysis. The variations in the environmental conditions and convection during P1 and P2 are consistent with a previous study showing that the Mascarene High generally inhibits convection owing to the trade inversion (Bovalo et al 2012). During the mature period of P4, a strong extratropical cyclone appears to the south of 20°S, and its appearance is synchronized with the local minimum pressure of less than 1008 hPa in the equatorial region and the intensification of the MJO convection (Fig.…”
Section: Large-scale Environmental Conditions Aroundsupporting
confidence: 90%
“…For the Atlantic respectively East Pacific) basin, the DEs ranged from 2.6% (respectively 0.9%) in 2005 to 20% (respectively 17.5%) in 2010. [ Bovalo et al , ] used the same method but found a smaller increase of the DE in the SWIO basin: from 2.0% in 2005 to 10.9% in 2013.…”
Section: Methodsmentioning
confidence: 99%
“…() have shown that precipitating convective systems on the African coast are mainly associated with the ITCZ, but are also influenced by local factors (orography, presence of lakes, oceanic influence) and by the southeasterly trade winds associated with the variability of the Mascarene High (Figure ). These two regions of strong deep convective activity also correspond to the location of the maximum lightning activity in the southwest Indian Ocean (Bovalo et al ., ), at (8°S–16°S; 35°E–40°E) and at (12°S–20°S; 45°E–50°E).…”
Section: Seasonal Cloud Distribution Over the Southwest Indian Oceanmentioning
confidence: 97%